Arab Credit Reporting Guide - International Finance Corporation; Arab Monetary Fund (International Finance Corporation, Washington, DC, 2017)
During the first decade of this century, from 2001 to 2010, attention focused on the development of the credit information industry in the Middle East and North Africa (MENA) region. As MENA’s role in the global economy increases along with its attendant demographic integration, the development of comprehensive information sharing systems across the region has become an imperative. The overall credit information system in the region requires reform at the initiative of stakeholders. Among the challenges are the diverse levels of technology, and lack of awareness and discipline in data collection. In response to traditional risk-assessment methods and, in some cases, a resistance to change, stakeholders have been encouraged to undertake innovative changes in the methods of risk evaluation being used by the credit industry. IFC and AMF commissioned the production of this guide to map progress and provide an overview of the credit reporting systems in the region. For the first time, an index representing a quantification of credit reporting in each country has been developed. To offer lessons learned, the guide highlights selected global trends and best practice for credit information sharing. The guide contains case studies of the 19 MENA countries with specific recommendations for local conditions.